2019
DOI: 10.28932/jmh.v2i3.1222
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Obesity on Blood Pressure in Early Adulthood and Middle Adulthood Males

Abstract: Hypertension is commonly found in obesity patients. Age affects the occurrence of hypertension. The aim of this study is to determine the effect of obesity on blood pressure levels in early adulthood males (<35 years) and middle adulthood males (?35 years). This is an observational analytic study using data from medical check-up records of male adult office workers in Bandung. The data was analyzed with Mann-Whitney test (? = 0.05) and Chi-Square to find the odds ratio (OR). The results showed that out of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Being overweight was shown to have an effect on increased blood pressure, since overweight people tend to find it more difficult to perform physical activities. Overweight people should make more effort to engage in activities so that blood pressure will decrease (Eusman, Ratnawati, & Elisabeth, 2019). A similar study was conducted by Vuvor (2017) which showed that, among Ghanaian adults aged 30-50 years, 28% of respondents who were overweight and/or obese also had high blood pressure.…”
Section: Relationship Between Nutritional Status and Hypertensionmentioning
confidence: 83%
“…Being overweight was shown to have an effect on increased blood pressure, since overweight people tend to find it more difficult to perform physical activities. Overweight people should make more effort to engage in activities so that blood pressure will decrease (Eusman, Ratnawati, & Elisabeth, 2019). A similar study was conducted by Vuvor (2017) which showed that, among Ghanaian adults aged 30-50 years, 28% of respondents who were overweight and/or obese also had high blood pressure.…”
Section: Relationship Between Nutritional Status and Hypertensionmentioning
confidence: 83%